THE IMPACT OF FEMALE ATTRACTIVENESS IN SPY - Veronika Juliani Pangjaya; Priska Febrinia Handojo (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This thesis discusses the impact of female attractiveness on the female character which is related to the way Spy sees attractive women and what the impacts to them are. There are criteria for female attractiveness that are displayed by the film such as physical attributes and traits. In order to show the criteria of attractive women and the responses that they get, I use stereotyping theory. Women who are physically attractive get better treatment, but in order to get that, they have to dress with a certain style that men favor. For the women who are considered as unattractive, they will be ignored by men. In conclusion, I find out that the appearance and the attitude of the female character still depend on men’s view. Women can also be seen as attractive from their characteristics. Attractiveness also has huge influences on the way women get treated by men.